Pengaruh Suhu dan Tekanan Penggorengan Terhadap Keripik Labu Kuning Menggunakan Mesin Vacuum Frying - Kuncoro, Sapto; Asmara, Sandi; Tamrin, Tamrin; Andayani, Siti (abe.fp.unila.ac.id, 2024)
In addition to other horticultural goods, Indonesia is a major producer of the pumpkin fruit that we see all the time. This fruit is often used to make a variety of foods, and it offers several health advantages. The transformation into dried food is a processing method with enormous commercial potential on a global scale. One of the specific post-harvest treatments required to increase the storage life of horticultural fruits like pumpkin is to convert it into chips. Vacuum frying is the preferred technique of processing these chips because it increases crispiness and prolongs the shelf life of the finished product. A new invention for the community at the research site is the use of a vacuum machine to process pumpkin chips. This is due to the practicality of the process and the ease of obtaining the raw ingredients. The purpose of this research is to find out how changing the temperature and pressure affects the pumpkin chip quality. The experiment was carried out with three different pressure levels (-66 cmHg, -68 cmHg, and -70 cmHg) with three different temperature changes (75 °C, 80 °C, and 85 °C). The approach used was a two-factor Randomized Block Design (RBD). Organoleptic evaluation, frying time, water content, and yield are some of the parameters measured. Pumpkin chip water content, frying time, and organoleptic test results are all affected by pressure and temperature, according to the findings. Fry for 41 minutes with a water content of 7% for the finest pumpkin chips. Keywords: Pressure, Pumpkin fruit, Temperature, Vacuum Frying.